Identification and characterization of novel sesquiterpene synthases TPS9 and TPS12 from Aquilaria sinensis - Yu, Cuicui; Gao, Shixi; Rong, Mei; Xiao, Mengjun; Xu, Yanhong; Wei, Jianhe (PeerJ, 2023)
Sesquiterpenes are characteristic components and important quality criterions for agarwood. Although sesquiterpenes are well-known to be biosynthesized by sesquiterpene synthases (TPSs), to date, only a few TPS genes involved in agarwood formation have been reported. Here, two new TPS genes, namely, TPS9 and TPS12, were isolated from Aquilaria sinensis (Lour.) Gilg, and their functions were examined in Escherichia coli BL21(DE3), with farnesyl pyrophosphate (FPP) and geranyl pyrophosphate (GPP) as the substrate of the corresponding enzyme activities. They were both identified as a multiproduct enzymes. After incubation with FPP, TPS9 liberated β-farnesene and cis-sesquisabinene hydrate as main products, with cedrol and another unidentified sesquiterpene as minor products. TPS12 catalyzes the formation of β-farnesene, nerolidol, γ-eudesmol, and hinesol. After incubation with GPP, TPS9 generated citronellol and geraniol as main products, with seven minor products. TPS12 converted GPP into four monoterpenes, with citral as the main product, and three minor products. Both TPS9 and TPS12 showed much higher expression in the two major tissues emitting floral volatiles: flowers and agarwood. Further, RT-PCR analysis showed TPS9 and TPS12 are typical genes mainly expressed during later stages of stress response, which is better known than that of chromone derivatives. This study will advance our understanding of agarwood formation and provide a solid theoretical foundation for clarifying its mechanism in A. sinensis.
Keywords: Sesquiterpene synthase; Plant; Gene identification; Aquilaria sinensis; Agarwood formation; Wounding-induced; Metabolites; Characterication function; Agarwood sesquiterpenes; Stress response